2022
DOI: 10.1128/jvi.00684-22
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Kaposi’s Sarcoma-Associated Herpesvirus ORF7 and Its Zinc-Finger Motif to Viral Genome Cleavage and Capsid Formation

Abstract: In herpesviral capsid formation, the viral terminase complex cleaves the TR sites on newly synthesized tandemly repeating genomes and inserts an appropriate genomic unit into an immature capsid. Herpes simplex virus 1 (HSV-1) UL28 is a subunit of the terminase complex that cleaves the replicated viral genome.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…However, we found that ORF7 interacted with both ORF29 and ORF67.5 (32). We also showed that ORF7-deficient KSHV formed numerous immature soccer ball-like capsids in the nucleus and failed to cleave the KSHV TR (33). The soccer ball-like capsid was a characteristic immature capsid that contains many particulate structures.…”
Section: Introductionmentioning
confidence: 78%
“…However, we found that ORF7 interacted with both ORF29 and ORF67.5 (32). We also showed that ORF7-deficient KSHV formed numerous immature soccer ball-like capsids in the nucleus and failed to cleave the KSHV TR (33). The soccer ball-like capsid was a characteristic immature capsid that contains many particulate structures.…”
Section: Introductionmentioning
confidence: 78%
“…To establish efficient recombinant virus-producing cells, tetracycline/doxycycline (Dox)-inducible (Tet-On) RTA/ORF50-expressing iSLK cells [ 47 , 48 , 49 ] or iVero cells [ 50 ] were used as recombinant KSHV-producing cells. For maintenance, iSLK cells were cultured in a growth medium containing 1 μg/mL of puromycin (InvivoGen, CA, USA) and 0.25 mg/mL of G418 (Nacalai Tesque, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The complementation assay was performed as previously described, but with several modifications [ 49 , 52 ]. The iSLK-21del cells (1 × 10 6 cells) were transfected with the 3×Flag-ORF21 plasmid using ScreenFect A plus (Wako) and treated with Dox and NaB.…”
Section: Methodsmentioning
confidence: 99%
“…To establish efficient recombinant virus-producing cells, tetracycline/doxycycline (Dox)-inducible (Tet-On) RTA/ORF50-expressing iSLK cells [47][48][49] or iVero cells [50] were used as recombinant KSHV-producing cells. For maintenance, iSLK cells were cultured in growth medium containing 1 μg/ml of puromycin (InvivoGen, CA, USA) and 0.25 mg/ml of G418 (Nacalai Tesque, Kyoto, Japan).…”
Section: Establishment Of Doxycycline-inducible Recombinant Kshv-expr...mentioning
confidence: 99%
“…The complementation assay was performed as previously described but with several modifications [49,52]. The iSLK-21del cells (1 × 106 cells) were transfected with 3xFlag-ORF21 plasmid using ScreenFect A plus (Fujifilm Wako Pure Chemical Corporation, Osaka, Japan) and treated with Dox and NaB.…”
Section: Complementation Assaymentioning
confidence: 99%